TRANSAKSI PERNIAGAAN SECARA ELEKTRONIK DALAM PERSPEKTIF HUKUM ISLAM - Nurhayati Nurhayati (Rumah Jurnal STAIN Majene, 2022)
This study discusses the review of Islamic law on electronic commercial transactions, along with the development of today's internet is an access that almost everyone uses and not a few people use it by buying and selling transactions. But the question is whether all transactions like this are allowed in Islam. In this paper, the writer limits the first two main problems: What is the basic concept of electronic commerce? and second, how is electronic commerce in terms of Islamic contract law?. The type of research used is library research using a normative approach. And the results of this study found that (1) basically the same as the agreement in general, the difference only lies in the media used in making the agreement. (2) electronic commerce in terms of Islamic engagement law is that as a whole, electronic commerce or e-commerce does not conflict with Islamic law, as long as it fulfils the things that must be contained in a contract according to Islamic Engagement Law. REFERENCES Ash Ahiddieqy, Teungku Muhammad Hasbi. (2000). Memahami Syariat Islam, cet.I. Semarang: Pustaka RRizki Putra. Baysir, Ahmad Azhar. (2000). Asas-asas Hukum Muamalat (Hukum Perdata Islam). Ed. Revisi. Yogyakarta: UII Press Yogyakarta.Cayber Law, Text ,andaCases, ”http://www.textshare.edu//service/training/resurce/glossary.html, diakses 5 Mei 2004. Dewi Gemala. (2005). Hukum Perikatan Islam di Indonesia, Cet. I, Jakarta: Kencana. Gerald Ferrera. (2005). The Internet & Cyber Law,” http://www.merchandisesemart.com/neocon/pros/pd06.htm, diakses 15 Januari 2021. Musbikin, Iman. (2001). Qawa’id Al-Fiqhiyah. Cet.1. Jakarta: Raja Grafindo Persada. Perwataatmadja, Karnaen A. (1996). Membumikan Ekonomi Islam di Indonesia. Cet. 1. Depok: Usaha Kami. Rahman, Afzalur. (1996) Doktrin Ekonomi Islam. Jilid 4, Yogyakarta: dana Bhakti Wakaf. Rasjid , Sulaiman (1996). Fiqh Islam. Cet. 29. Bandung: Sinar Baru Algasindo. Suharnoko. (2004). Hukum Perjanjian –teori dan Analisis Kasus, Jakarta: Kencana. Taqyuddin an-Nabhani. (1996). Membangun Sistem Ekonomi Alternatif Perspektif Islam (An-Nidlam Al-Iqtishadi Fil Islam) diterjemahkan oleh Magfur Wachid, Surabaya: Risalah Gusti.